Penerapan Model Kooperatif Tipe Group Investigation Pada Pembelajaran Matematika Materi Statistika - Valentsia Gabrela Katihokang; Philotheus E.A. Tuerah; Patricia V.J. Runtu (Departement of Mathematics Education, 2024)
This article aims to describe the application of Group Investigation type cooperative model to improve mathematics learning outcomes with statistics material in class VIII SMP NEGERI 2 MANADO. This type of research uses Quasi Experiment research. The population of this study was class VIII of SMP Negeri 2 Manado, 2 samples were selected, namely class VIII-1 as an experimental class with a total of 28 students and class VIII-3 as a control class with a total of 22 students. The research design used was Posttest-Only Control Design. The average value of the Posttest for the experimental class was 80.3571 and for the control class was 64.1363. Based on the results of research conducted in both classes using hypothesis testing, namely the t test with a significance level of 5%, it was found that then was rejected so that was accepted. Thus it can be concluded that student learning outcomes on Data Concentration Measures and Data Distribution Measures using the Group Investigation type cooperative learning model are better than using the direct learning model.